2002
DOI: 10.1016/s0005-2736(02)00339-5
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical consequences of linker chemistry and polymer size on stealth erythrocytes: size does matter

Abstract: Immunocamouflaged red blood cells (RBC) are produced by cell surface derivatization with methoxypolyethylene glycol (mPEG). These immunologically attenuated cells may reduce the risk of allosensitization in chronically transfused patients. To characterize the effects of differing linker chemistries and polymer lengths, RBC were modified with cyanuric chloride activated mPEG (C-mPEG 5 kDa), benzotriazole carbonate methoxyPEG (BTC-mPEG; 5 or 20 kDa) or N-hydroxysuccinimidyl ester of mPEG propionic acid (SPA-mPEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 22 publications
6
113
0
Order By: Relevance
“…Previous studies have shown that hydrophilic surfaces have decreased total protein adsorption and are also more biocompatible [12]. Thus, mPEG grafting generates a steric barrier while simultaneously biophysically camouflaging surface charge thus reducing immune recognition of implantable biomaterials, allogeneic red blood cells [5,[13][14][15][16][17][18], lymphocytes [3,4,[19][20][21] and viruses ( Figure 6BD) [22]. As shown in this study, consequent to PEGylation, latex particles demonstrated significant inhibition of protein adsorption in a polymer doseand length-dependent manner, as measured quantitatively with colorimetric protein assay and flow cytometry ( Figure 2A and B) and qualitatively by SDS-PAGE, fluorescent microscopy and iTRAQ-MS analysis (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hydrophilic surfaces have decreased total protein adsorption and are also more biocompatible [12]. Thus, mPEG grafting generates a steric barrier while simultaneously biophysically camouflaging surface charge thus reducing immune recognition of implantable biomaterials, allogeneic red blood cells [5,[13][14][15][16][17][18], lymphocytes [3,4,[19][20][21] and viruses ( Figure 6BD) [22]. As shown in this study, consequent to PEGylation, latex particles demonstrated significant inhibition of protein adsorption in a polymer doseand length-dependent manner, as measured quantitatively with colorimetric protein assay and flow cytometry ( Figure 2A and B) and qualitatively by SDS-PAGE, fluorescent microscopy and iTRAQ-MS analysis (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…To quantitate the degree of immunocamouflage induced by the grafted polymers, flow cytometry (FACSCalibur; BD Biosciences San Jose, CA, USA) was performed using previously established erythrocyte parameters [12][13][14]. A minimum of 20000 cells was analyzed per sample.…”
Section: Detection Of Blood Group Antigens By Flow Cytometrymentioning
confidence: 99%
“…To examine the effects of the various mPEG derivatives in vivo, RBC survival studies were performed in Balb/c mice [9,12,13]. All animal studies were institutionally approved and conducted in compliance with all applicable Canadian animal care regulations.…”
Section: In Vivo Rbc Survival Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…When universal donor is not available, the conversion of A or B type to universal type is an alternative to overcome the life-threatening situation. For this reason multi-dimensional research works have already been initiated to camoufl age the RBCs [4][5][6][7]. However , there remain various drawbacks in new techniques including development of neoantigen, formation of PEG antibodies against mPEGylated erythrocyte, high chances of phagocytic recognition, poor oxygen diffusion, incomplete loss of antigenicity of A, B blood types [8].…”
Section: Introductionmentioning
confidence: 99%